Advances in hypothalamic hamartoma research over the past 30 years (1992–2021): a bibliometric analysis - Lu, Di; Wang, Tianren; Yang, Yanfeng; Fan, Xiaotong; Chen, Sichang; Wei, Penghu; Shan, Yongzhi; Zhao, Guoguang (Frontiers in Neurology, 2023)
Background: Hypothalamic hamartoma (HH) is a rare intracranial disease whose manifestations include gelastic seizures and precocious puberty. The diagnosis and treatment of HH have changed substantially over the past three decades as medical care has improved. Bibliometrics can reveal the evolution and development of a scientific field. Methods: Documents on HH were retrieved from the Web of Science Core Collection (WoSCC) database on August 23, 2022. The search terms were as follows: “hypothalamic hamartoma” or “hamartoma of the hypothalamus” or “hypothalamic hamartomas”. The types of documents were restricted to articles, case reports, and reviews. VOSviewer, CiteSpace, and the R package “bibliometrix” were used for a bibliometric analysis. Results: A total of 667 independent documents on HH were obtained from the WoSCC database. The most common types of documents were articles (n = 498, 75%) and reviews (n = 103, 15%). The number of annual publications fluctuated but showed an upward trend overall, and the annual growth rate was 6.85%. The cumulative publication data indicated that the most influential journals in the HH field include Epilepsia, Epileptic Disorders, Child’s Nervous System, Neurosurgery, and the Journal of Neurosurgery. Kerrigan JF, Ng YT, Rekate HL, Regis J, and Kameyama S were among the most prominent authors in the field of HH, with numerous publications and citations. American research institutions, especially the Barrow Neurological Institute, occupied a pivotal position in HH research. Other countries and institutions were catching up and producing considerable research results. Research on HH has steadily switched its emphasis from Pallister-Hall syndrome (PHS) and precocious puberty to epilepsy and new diagnostic and therapeutic techniques, including Gamma Knife, laser ablation, and interstitial thermal therapy. Conclusion: HH remains a special neurological disease with significant research prospects. The development of novel technologies, including MRI-guided laser-induced thermal therapy (MRg-LiTT) and stereotactic radiofrequency thermocoagulation (RF-TC), has enabled the efficient treatment of gelastic seizures in HH while minimizing the risks associated with craniotomies. Through bibliometric analysis, this study points out the direction for future HH research.